Development of a multilingual intelligent project planning and monitoring system - Teslia, Iurii; Yehorchenkova, Nataliia; Yehorchenkov, Oleksii; Khlevna, Iulia; Kataieva, Yevheniia; Klievanna, Ganna; Khlevnyi, Andrii; Latysheva, Tatiana; Ivanov, Ivan; Sazonov, Anton (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research of this work is the processes of project planning and monitoring. The solved problem is the development of a model, method and structures of a multilingual intelligent project planning and monitoring system and its experimental verification of the ability to understand the statements of managers in different languages. The requirements for such a system are formulated. An analysis of the existing theoretical and practical developments in this area was carried out. It was established that there are no developments in the field of project management that can adapt to new natural languages. It was found that the formulated requirements can be satisfied within the framework of the reflexive approach. It is characterized by simplicity, continuity, and insensitivity to errors in natural language statements. To confirm these assumptions, an experimental multilingual project planning and monitoring system and experimental research methodology were developed. The results of the experiments obtained during the use of the created experimental system testify to the correct identification of the content of appeals to the intellectual system in 6 languages with a probability higher than 0.99, and to recognize the structure of statements with a probability higher than 0.98. And the time for configuring the system to work with a new language did not exceed 1 hour. This allows to use it for practical work in distributed management systems for remote interaction of managers and specialists with the system in different languages. The conducted experiments confirmed the assumption about the effectiveness of the reflexive approach for creating project management systems. The developed model, method, structures, and system can be used for different types of projects, such as regional development projects, IT, etc.